2002
DOI: 10.1007/s007950200000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of apoptotic cell death in autoimmune diseases

Abstract: A low rate of as well as a high rate of apoptotic cell death is involved in the development of various human autoimmune diseases. In rheumatoid arthritis (RA), impaired apoptosis of rheumatoid synovial cells appears to induce hyperplasia of the synovial tissues, whereas the acceleration of apoptotic cell death of osteoblasts may contribute to periarticular bone loss in patients with RA. Humoral factors including cytokines and growth factors present in the rheumatoid synovial tissues modulate the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…This active process involves cellular metabolism with gene activation and protein synthesis. It is assumed that the expression of apoptosis-related molecules is affected by numerous humoral and cellular factors [1]. Disorders in the regulation of programmed cell death that hinder elimination of cells reacting with their own antigen and thus promote their excessive proliferation constitute a major link in the development of many diseases, including autoimmune disorders of the thyroid [2].…”
Section: Introductionmentioning
confidence: 99%
“…This active process involves cellular metabolism with gene activation and protein synthesis. It is assumed that the expression of apoptosis-related molecules is affected by numerous humoral and cellular factors [1]. Disorders in the regulation of programmed cell death that hinder elimination of cells reacting with their own antigen and thus promote their excessive proliferation constitute a major link in the development of many diseases, including autoimmune disorders of the thyroid [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that significant expression of TIAR may indicate on enhanced activity of egzogenous way of apoptosis in autoimmune diseases, for example in GD. Kawakami et al observed the association between the apoptosis of thyrocytes and the process of autoimmune thyroid diseases and suggested that Fas-mediated apoptosis of human thyrocytes is modulated by thyroid-stimulating antibodies, thyroid stimulation blocking antibodies and cytokines [20]. Similarly, we conclude that elevated expression of NIS and TPO in Graves' disease is associated with higher stimulation and activation of apoptosis in thyroid follicular cells during autoimmune process.…”
Section: Discussionmentioning
confidence: 67%
“…This indicates that apart from CD64 expression, activation of target cells may be a prerequisite for the cytotoxic effect of CD64-RiA. Recent work indicates that insufficient apoptosis of inflammatory cells in RA joints might contribute to pathogenesis (27,28). Besides selective elimination, a strong inhibition of proinflammatory cytokines like TNF-␣ and IL-1␤ was observed (21).…”
Section: Discussionmentioning
confidence: 96%